2022
DOI: 10.3390/polym14050964
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Chemical Composition and Structure of Birch Phloem Dioxane Lignin: A Comprehensive Study

Abstract: Understanding the chemical structure of lignin in the plant phloem contributes to the systematics of lignins of various biological origins, as well as the development of plant biomass valorization. In this study, the structure of the lignin from birch phloem has been characterized using the combination of three analytical techniques, including 2D NMR, Py-GC/MS, and APPI-Orbitrap-HRMS. Due to the specifics of the phloem chemical composition, two lignin preparations were analyzed: a sample obtained as dioxane li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been reported that dioxane lignin can be extracted with tannins and fatty acids from the bark of spruce or birch. 47,48 In WW, the disappearance of the peak centering around 20 ppm in WW_N can be attributed to the C4–C8 of the inter-flavonoid linkages of tannins or fats, and these were completely removed after the 0.1 M NaOH treatment 48 (Fig. 5).…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that dioxane lignin can be extracted with tannins and fatty acids from the bark of spruce or birch. 47,48 In WW, the disappearance of the peak centering around 20 ppm in WW_N can be attributed to the C4–C8 of the inter-flavonoid linkages of tannins or fats, and these were completely removed after the 0.1 M NaOH treatment 48 (Fig. 5).…”
Section: Resultsmentioning
confidence: 97%
“…For the primary screening of the chemical composition of the P. commune acetone extract, the combination of the two-dimensional NMR spectroscopy and the computational expert system for processing the obtained data, which was proven in a recent study of polyphenolic compounds in birch phloem [ 18 ], was used. This made it possible to isolate the signals of individual components of a complex mixture and presumably identify them on the basis of a library search.…”
Section: Resultsmentioning
confidence: 99%
“…This study is an attempt to fill this gap and is aimed at a comparative characterization of the aqueous ethanol extracts of cloudberry fruits and leaves, as well as a comprehensive study of the chemical composition and antioxidant activity of leaf secondary metabolites. Its methodological basis is formed by the combination of the most powerful and complementary techniques of two-dimensional NMR spectroscopy and high-performance liquid chromatography–high-resolution mass spectrometry, which has already proven itself in solving problems with regard to non-targeted screening and the identification of extractive substances of moss, compression wood, and birch phloem polyphenols [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%